Epidemiology and disease characteristics of myelofibrosis: a comparative analysis between Italy and global perspectives - Breccia, Massimo; Palandri, Francesca; Polverelli, Nicola; Caira, Morena; Berluti, Michela; Palumbo, Giuseppe A.; De Stefano, Valerio (Frontiers in Oncology, 2024)
Myelofibrosis (MF) is a clonal disorder of hematopoietic stem cells characterized by altered bone marrow function and fibrosis. The aim of this narrative review is to report on the most recent epidemiologic data and to discuss features of MF and current strategies for the management of this condition in clinical practice. MF features covered by our review will include: characteristics of patients with MF; myeloproliferative and myelodepletive phenotypes; MF-associated thrombosis and bleeding; risk of infections; prefibrotic and overt PMF; secondary MF. Finally, we will discuss a few aspects of MF management in clinical practice and suggest strategies for its optimization and standardization. The focus of our paper is on Italy, but relevant data from other countries will also be reviewed.